C-reactive Protein Versus Neutrophil/lymphocyte Ratio in Differentiating Bacterial and Non-bacterial Pneumonia in Children - Gauchan, Eva; Adhikari, Sudhir (Journal of Nepal Health Research Council, 2017)
Background: Pneumonia is a leading cause of childhood mortality in a low resource country. Simple laboratory markers can help differentiate between bacterial and non-bacterial pneumonias for appropriate management. Methods: In children aged one to 60 months with features of lower respiratory infection, C-reactive protein (CRP) and neutrophil-lymphocyte ratio (NLR) were used to differentiate between bacterial and non-bacterial pneumonias. The cutoff values for detecting bacterial pneumonias were evaluated by statistical tools.Results: Bacterial pneumonia was diagnosed in 285 (43.6%) children out of 654 studied. At a cut-off value of 36 mg/L CRP was predictive of bacterial pneumonias with sensitivity and specificity of 61.8% and 91.3% respectively while the sensitivity and specificity for predicting bacterial pneumonia using NLR was 45.6% and 64% respectively with 1.28 used as a cut-off.Conclusions: Our study shows that CRP is superior to NLR in differentiating bacterial from non-bacterial pneumonias in children. Keywords: Bacterial and non-bacterial pneumonia; C-reactive protein; neutrophil to lymphocyte ratio.